Assessing peri-urban livelihood vulnerability to natural hazard : an evidence-based study of sdissected Himalayan terrain, Nepal - Thapa, Shreesha; Pramanik, Malay; Vilas Nitivattananon; Shrestha, Rajendra P.; AIT scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
Nepal{u2019}s dissected Himalayan terrain, characterized by steep slopes and intense monsoon systems, places peri-urban municipalities at considerable risk of floods and landslides. This study assessed the livelihood vulnerability of communities in Banepa, Panauti, Dhulikhel, and Namobuddha municipalities of Kavrepalanchok by applying the Livelihood Vulnerability Index (LVI) framework. Primary data were collected through household surveys of 381 households across 47 wards, along with key informant interviews to understand local perspectives. The study used a composite index approach to calculate LVI scores, integrating indicators of exposure, sensitivity, and adaptive capacity. Geographic Information Systems (GIS) were used to map vulnerability patterns, while logistic regression analysis identified key socio-economic and institutional factors influencing vulnerability.The findings showed clear differences linked to geographic context. The steep hill wards in Namobuddha had the highest composite LVI at 0.61, driven by high exposure (0.70) and low adaptive capacity (0.44). The floodplain wards in Panauti recorded a composite LVI of 0.57, reflecting frequent flooding and limited coping mechanisms. Banepa and Dhulikhel, as urban hill centers, had comparatively lower vulnerability scores around 0.50, but still faced sensitivity due to infrastructure gaps and livelihood dependence on local markets. Regression analysis revealed that households led by individuals with only primary education were 2.3 times more likely to be highly vulnerable, while lack of cooperative membership increased vulnerability by 1.8 times. Only 12 percent of surveyed households had insurance and less than 15 percent received government support after disasters. By integrating quantitative analysis with institutional insights, the research contributes to climate adaptation planning and evidence-based policy development in Nepal{u2019}s hazard-prone peri-urban settings.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Urban Innovation and Sustainability
Thesis (M. Sc.) - Asian Institute of Technology, 2025
Keywords: Hazardous geographic environments -- Himalaya Moutains Region; Climatic changes -- Himalaya Moutains Region; Geographic Information Systems